Timing of household food insecurity exposures and asthma in a cohort of US school-aged children. Issue 11 (22nd February 2019) - Mangini, Lauren D; Hayward, Mark D; Zhu, Yeyi; Dong, Yongquan; Forman, Michele R
Abstract : Objective: Food insecurity is positively associated with asthma, the most common chronic childhood disease, yet directionality is unclear. The objective was to determine the association between exposure to food insecurity in early childhood and the odds of asthma later in childhood. Design: Data from four waves of the Early Childhood Longitudinal Study-Kindergarten (ECLS-K) cohort, a prospective, dual-frame, multistage probability cluster sampling study of school-aged US children were entered in multivariate logistic regression models, adjusted for covariates. Exposures to food insecurity were based on parental responses to the validated USDA 18-item module at each wave. Setting: Public and private primary and secondary schools between 1998 and 2007. Participants: At its inception (1999), the ECLS-K had 20 578 kindergarteners; by the spring of eighth grade (2007), the cohort dropped to 9725 due to attrition. Children missing an exposure, outcome or confounding variable were excluded, final n=6731. Primary outcome measure: Child's diagnosis of asthma by a healthcare professional as reported by the parent. Results: Household food insecurity (vs food security) in the year before kindergarten and in second grade had a higher odds of asthma by 18% (95% CI 1.17 to 1.20) and 55% (95% CI 1.51 to 1.55). After removing asthmatics before third grade from the model, food insecurity in second grade was associated with higher odds of asthma at fifth or eighth grades (OR 1.55; 95% CI 1.53 to 1.58), whereas food insecurity in the year before kindergarten had a lower odds at fifth or eighth grades. Conclusions: Food insecurity in the year before kindergarten and in second grade were associated with a higher odds of asthma in third grade. Food insecurity in second grade retained the signal for increased odds of asthma after third and through eighth grades. Additional research is needed to explore childhood windows of vulnerability to asthma.